The two faces of a myth: the Frankenstein myth and its mythological heritage - Alves, Talita (Em Tese, 2014)
Frankenstein, written by Mary Shelley, alludes to the mythological figure of Prometheus since the subtitle of the novel. Frankenstein is a modern Prometheus, adjusted to the Romantic patterns of the time it was written. Like Prometheus, Frankenstein is also the creator of a new being; however his creature becomes an uncontrollable monster, which highlights human fallibility. Prometheus is not the only myth used by Mary Shelley to compose her work; she also alludes to the Christian story of creation and fall of mankind through John Milton’s Paradise Lost. Frankenstein and his creature can be compared to several Paradise Lost’s characters in different parts of the novel. Despite the allusions to Paradise Lost and Prometheus, Frankenstein is not a mere repetition of these myths, the story of a scientist who creates a monster became a Romantic myth that remains alive in people’s imaginary.